MENGIDENTIFIKASI KEBAKARAN KMP TRANSHIP I DAN LANGKAH PREVENTIF UNTUK MENCEGAH TERJADINYA KEBAKARAN SESUAI INTERNATIONAL SAFETY MANAGEMENT (ISM) CODE - yulianto, yulianto; Santoso, Wahyudi (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2024)
The fire accident experienced by KMP Tranship I on October 2023, when sailing from Merak Harbor, Banten to Bakauheni Harbor, Lampung Lampung left trauma and bad experiences for the crew and passengers, so the fire that occurred must be identified by the crew regarding causes and methods of control. In preventing fires, there is a need for technical instructions or international regulations as a guide. The aim of this research is to know and identify before and after a fire occurs on a ship to minimizecasualties and the risk of increasing the size of the fire by implementing existing rules appropriately and measurably based on the International Safety Management (ISM) Code. The research method carried out was by exploring several sources in the field including the crew of the KMP Tranship I ship, the South Lampung Police Port Sector Unit (KSKP), River, Lake and Ferry Transport (ASDP) and the Fire Brigade (Damkar) team. including field observations regarding fires, and literacy from various books. The results of the research are that by implementing the International Safety Management (ISM) Code standards, continuously and well controlled, the ship's crew will be able to assess the risk (risk assessment) of each ship accident, including ship fires and losses experienced by the ship.